Increased Plasma Heme Oxygenase-1 Levels in Patients With Early-Stage Parkinson’s Disease - Sun, Wenhua; Zheng, Jinhua; Ma, Jianjun; Wang, Zhidong; Shi, Xiaoxue; Li, Mingjian; Huang, Shen; Hu, Shiyu; Zhao, Zhenxiang; Li, Dongsheng (Frontiers in Aging Neuroscience, 2021)
Introduction: Heme oxygenase-1 (HO-1) is a 32 kDa stress-response protein implicated in the pathogenesis of Parkinson’s disease (PD). Biliverdin is derived from heme through a reaction mediated by HO-1 and protects cells from oxidative stress. However, iron and carbon monoxide produced by the catabolism of HO-1 exert detrimental effects on patients with PD. The purpose of this study was to determine whether plasma HO-1 levels represent a biomarker of PD and to further explore the underlying mechanism of increased HO-1 levels by applying voxel-based morphometry (VBM).Methods: We measured plasma HO-1 levels using an enzyme-linked immunosorbent assay (ELISA) in 156 subjects, including 81 patients with early- and advanced-stage PD and 75 subjects without PD. The analyses were adjusted to control for confounders such as age, sex, and medication. We analyzed T1-weighted magnetic resonance imaging (MRI) data from 74 patients with PD using VBM to elucidate the association between altered brain volumes and HO-1 levels. Then, we compared performance on MMSE sub-items between PD patients with low and high levels of HO-1 using Mann-Whitney U tests.Results: Plasma HO-1 levels were significantly elevated in PD patients, predominantly those with early-stage PD, compared with controls (p < 0.05). The optimal cutoff value for patients with early PD was 2.245 ng/ml HO-1 [area under the curve (AUC) = 0.654]. Plasma HO-1 levels were unaffected by sex, age, and medications (p > 0.05). The right hippocampal volume was decreased in the subset of PD patients with high HO-1 levels (p < 0.05). A weak correlation was observed between right hippocampal volume and plasma HO-1 levels (r = −0.273, p = 0.018). There was no difference in total MMSE scores between the low- and high-HO-1 groups (p > 0.05), but the high-HO-1 group had higher language scores than the low-HO-1 group (p < 0.05).Conclusions: Plasma HO-1 levels may be a promising biomarker of early PD. Moreover, a high plasma concentration of the HO-1 protein is associated with a reduction in right hippocampal volume.